Blending the Optical and Redox Properties of Oligoynes and Boron Difluoride Formazanates. Issue 39 (18th August 2022) - Dhindsa, Jasveer S.; Cotterill, Erin L.; Buguis, Francis L.; Anghel, Michael; Boyle, Paul D.; Gilroy, Joe B.
Abstract: Oligoynes and polyynes are 1D chains of conjugated sp ‐hybridized carbon atoms consisting of alternating single and triple bonds. Their stability rapidly decreases with increasing chain length beyond only a few repeating units. Design strategies, such as the use of bulky end‐capping groups, allow for their characterization and isolation while not contributing significantly to their physical properties. In this study, we incorporate redox‐active BF2 formazanate dyes (BF2 ) as end‐caps to prepare symmetric (BF2 −[C≡C] n −BF2 ) and asymmetric (BF2 −[C≡C] n −Si( i Pr)3 ) families of oligoynes containing up to 10 alkyne units. In doing so, we introduce stable oligoynes that possess a blend of optical and redox properties that cannot be achieved by either oligoynes or BF2 formazanates individually (e.g., panchromatic absorption, multiple and tunable reversible redox waves). This approach is transferable to other functional end‐caps to facilitate the preparation of π‐conjugated materials with utility in the organic electronics arena. Abstract : Redox‐active boron difluoride formazanate end‐caps are used to stabilize symmetric and asymmetric families of oligoynes containing between 2 and 10 alkyne units. These oligoyne‐dye conjugates exhibit multiple redox waves and panchromatic absorption profiles.